What are junior high maths students' Edmodo interests and learning outcomes? - Shania, Faridatus; Inganah, Siti; Rosyadi, Alfiani Athma Putri; Afolaranmi, Adebayo Ola (Journal of Teaching and Learning Mathematics, 2024)
This research aims to describe students' interests and learning outcomes after using the Edmodo application. This type of research is descriptive by categorizing and using a quantitative approach. The subjects of this research were class VIIB students at SMP Negeri 2 Tegalsari. To see students' interest after studying using Edmodo through data obtained from learning interest questionnaires and interviews given to students. Meanwhile, it is obtained from the quiz/test scores to see student learning outcomes. Based on the results of data analysis, it was found that the use of the Edmodo application in mathematics learning went according to expectations seen from student participation from the beginning of the learning activity to the end and was following the RPP, so it could be said to be quite successful. The students' learning interest results are categorized as good because they meet the three predetermined indicators: feelings of joy, attention, interest, and involvement. Student learning outcomes are also classified as having a reasonably good score so that it can be said that students can understand the learning material and solve problems well.